1986
DOI: 10.1136/jnnp.49.11.1266
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of motor planning in patients with Parkinson's disease: evidence from ideomotor apraxia testing.

Abstract: Ideomotor apraxia has been defined as a failure to produce either a correct movement on verbal cornmand or to imitate correctly a movement performed by the examiner when the incorrect performance cannot be explained by weakness, incoordination, akinesia, abnormal reflexes, impaired auditory comprehension, or impaired visual or tactile perception.1 This had led to the conclusion that ideomotor apraxia is an inaccurate term to associate with Parkinson's disease because the patients manifest motor deficits.2With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
2
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 17 publications
0
38
2
3
Order By: Relevance
“…The high frequency of pantomimic apraxia in HD, observed in our present study and in those by Hodl et al [17] and Hamilton et al [16] , is higher than has been observed previously in several studies of ideomotor limb apraxia in patients with other diseases of the basal ganglia [30][31][32][33][34] . For instance, Leiguarda and Marsen [35] reported pantomimic movement apraxia in 2/8 patients with Parkinson's disease and 2/5 patients with progressive supranuclear palsy.…”
Section: Discussioncontrasting
confidence: 56%
“…The high frequency of pantomimic apraxia in HD, observed in our present study and in those by Hodl et al [17] and Hamilton et al [16] , is higher than has been observed previously in several studies of ideomotor limb apraxia in patients with other diseases of the basal ganglia [30][31][32][33][34] . For instance, Leiguarda and Marsen [35] reported pantomimic movement apraxia in 2/8 patients with Parkinson's disease and 2/5 patients with progressive supranuclear palsy.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding may reflect the Parkinson disorder in design and execution of motor plans (Goldenberg et al, 1986) so that these patients are unable to learn new movement patterns.…”
Section: Discussionmentioning
confidence: 89%
“…[45][46][47] Likewise, apraxia is not a common feature of PD-D, 39 although impaired ideomotor praxis was described in an unselected population of patients with PD. 48 Many of the described language deficits (such as impaired verbal fluency, naming difficulty), however, may not reflect a true involvement of language functions but may be related to the dysexecutive syndrome, i.e., impaired self-generated search strategies due to executive dysfunction. 30,47 Behavioural and personality changes are frequent in patients with PD-D. All patients with PD-D had clinical and historical evidence of personality changes, 29 depressive symptoms were especially common, more so than in patients with AD.…”
Section: S64mentioning
confidence: 98%